Estado, comunidades autónomas y acción exterior en el ordenamiento constitucional español - Fernández Segado, Francisco (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
The article 149.1.3 of the Spanish Constitution attributes to the State the exclusive scope about the international relations. This clause was initially interpreted in way extremeley strict in favour of the State, but the Spanish Constitutional Court has subsequently changed its position. The Court has interpreted that it’s not suitable to identify the matter «international relations» with any kind of activities of foreign projection as such expansive interpretation would finish for confering the State’s scope every measure or action which it be gifted of some foreign repercusion even if it be remote with subsequent reorganization of the constitutional system of scope’s distribution between the State and the Autonomous Communities.